Integrasi Agama dan Sains dalam Perspektif Ziaudin Sardar Solusif-Sintesisnya terhadap Problematika Pendidikan Islam - Mohd Fauzan; Amril M (Journal on Education, 2024)
This article aims to discuss the integration of religion and science as a solution and synthesis of educational problems from Ziaudin Sardar's perspective. The problems in this article are examined using the Literature Review approach. The literature used comes from relevant journal articles. Based on the discussion, it can be concluded that the integration of religion and science according to Ziauddin Sardar as a solution in the development of Islamic educational thought by building an Islamic epistemology by developing a new paradigm in which the external expressions of Islamic civilization which include science, technology, politics, relations between nations, and the development of national society, can studied and developed for practical human needs according to contemporary realities.